Market Structure and Efficiency of QISMUT Banking Sector - Noor-Shazreen, Mortadza; Rossazana Ab-Rahim, Ab-Rahim; Alim, Dee (Human Resource Management Academic Research Society, 2019)
The aim of this study is to assess the market structure and efficiency of QISMUT (Qatar, Indonesia, Saudi Arabia, Malaysia, United Arab Emirates and Turkey) banking market over the study period of 2006 to 2016. Concentration ratio and Herfindahl-Hirshman Index are used to measure market structure while efficiency is measured using Data Envelopment Analysis (DEA). The results show conventional banks in QISMUT are more concentrated than its Counterpart, the Islamic banks. However, Islamic banks are found to be more efficient than the conventional banks. Keywords: Market Structure, Efficiency, QISMUT, Banking Market.